Single-Channel Seismic Images from Caribbean Sea and Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC1112 (1967) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC1112 conducted in 1967 (Chief Scientist: Dr. George Bryan). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition.